Appropriate age at solid introduction: is EFSA extending the individualised window on a sounding scientific evidence?. (17th February 2021) - Dipasquale, Valeria; Agostoni, Carlo; Romano, Claudio
Abstract: The appropriate age at introduction of complementary foods (CFs) has always been a matter of debate. The Panel on Nutrition, Novel Foods and Food Allergens (NDA) of the European Food Safety Authority (EFSA) recently produced a Scientific Opinion based on a systematic literature search, supporting the existence of an age range for the introduction of CFs, which vary according to the characteristics of the individual. Furthermore, it concluded that the early introduction of CFs is not associated with either adverse or beneficial health effects at any age. The introduction of foods of age-appropriate texture and nutritional properties might be enough for reaching both developmental and nutritional goals. Accordingly, complementary feeding could be implemented as an infant-tailored approach, guided by the acquisition of the neuromotor skills necessary to progress from a liquid to a diversified diet.